Growth and population dynamics of Catenaria anguilluiae in relation to oilcakes - and R.C. GUPTA, K.P. SINGH, P. BANDYOPADHYAY, S.S. VAISH, T. MAKESH KUMAR (Indian Phytopathology, 2002)
Radial growth of seven isolates of Catenaria anguillulae was studied on beef extract agar and oilcake agar media. The oilcake agar consisted of linseed, mustard, sesamum, neem and mahua cake each @ 0.5 %. On beef extract agar, of all the seven isolates, I and VII were fast growing while isolate VI was slow growing. The other isolates, viz., isolate II, III, IV and V showed moderate growth on beef extract agar medium. All the isolates grew well on oilcake media except on mahua, which did not allow any growth of the fur.gus. The maximum growth of most of the isolates occurred on mustard or linseed oilcake agar medium followed by beef extract agar medium. Neem oilcake agar medium supported the minimum growth of the fungus. Further the effect of mustard, linseed, neem and sesamum oilcakes on C. anguillulae in soil was studied by amending the soil around the roots of citrus, mango and chilli plants. The population of C. enquiltulee increased several folds in soils amended with oilcakes.